Their determination to remain a Cherokee community's resistance to the Trail of Tears in North Carolina - Greene, Lance, 1963- (Indians and southern history., 2022)
"This book tells the remarkable story of a Cherokee community in the mountains of North Carolina who survived the aftermath of the Trail of Tears. The story is explored through the lives of wealthy plantation owners Betty and John Welch and the members of their extended family. John was Cherokee, and Betty was White. Their farm, which included nine enslaved Africans, was on the northeastern edge of the Cherokee Nation at the time of the Cherokee removal of 1838. During removal, the Welches assisted roughly 150 more traditional Cherokees hiding in the steep mountains. After the removal, the Welches provided land for these families to rebuild a community, Welch's Town. From 1839 to 1855 the Welch plantation and Welch's Town functioned as distinct but tightly connected communities"--